System Literature Review : Analisis Gelombang Medan Elektromagnetik dan Seismik yang Ditimbulkan oleh Gejala Gempa - Ardiansyah Ardiansyah; Tiara Pramesti Wulandari; Muhammad Ziddan Al Fariz; Raihan Ahmad Musyaffa; Diyajeng Luluk Karlina (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
One of the most seismically active countries in the world is Indonesia. One of the few countries located in the Southeast Asian Seismic Zone is Indonesia. It is difficult to predict when and how an earthquake will occur as earthquakes are natural events. Various studies on earthquake precursors have been conducted with different results. The purpose of this paper is to examine the calculation of earthquakes using electromagnetic and seismic beats. To compile this article, we used the literature study method from various relevant national and international journals. The results concluded that, electromagnetic waves are easily excited even by weak seismic vibrations in the earth's crust, and they can be identified easily both above and below the ground surface.